Características produtivas e estruturais dos capins cayana, marandu e sabiá submetidos ao diferimento - Oliveira, Jociel Batista de (2024)
Pasture deferral consists on a relatively low-cost strategy, little widespread in the Northeast region, in addition to being used to mitigate the seasonality of forage production in pastures, especially during the dry season. In this sense, this paper has the objective of evaluating the productive and structural characteristics of grasses of the genus Urochloa syn. Brachiaria (Urochloa brizantha cv. Marandu, Urochloa hybrida cv. Cayana and cv. Sabiá) in deferral. The activity was developed at the Rural Campus of the Federal University of Sergipe in São Cristóvão/SE. The pastures were deferred in September, 15 cm high, remaining deferred (without defoliation) for 68 days (until November), in the years 2022 and 2023. The experimental design was carried out in randomized blocks, with three replications, totaling 9 units experimental (plots of 15 m²). In 2023, Marandu grass demonstrated taller heights compared to other varieties. It is important to highlight the significant increase in tipping observed in Marandu. The tiller population density was influenced by the forage plant, with greater emphasis on Cayana in 2022 and different tiller heights in 2023. Marandu grass had a lower accumulation of leaf blades and dead forage in 2022, while Cayana stood out with lower total accumulation of forage and leaf blades, but greater accumulation of stalks, in 2023. Percentages of leaf blades, stalks and dead forage were influenced by the interaction between forage plant and the deferral period. Population density of basal tillers was higher in Cayana grass, while Marandu showed lower population density of total tillers. Therefore, it can be concluded that Cayana and Sabiá grasses have a greater number of tillers than Marandu grass. These grasses also differ in the location of the tillers, with Marandu grass having more tillers that are located in the upper portion of the canopy. Sabiá and Cayana grasses have high forage production, being an alternative to Marandu grass.